True mid-infrared Pr3+ absorption cross-section in a selenide-chalcogenide host-glass - Seddon, Angela B.; Furniss, David; Tang, Z.Q.; Sójka, L.; Benson, Trevor M.; Caspary, R.; Sujecki, S. (2016)
The mid-infrared (MIR) spans the 3-25 m wavelength range. Rare-earth-ion doped selenide-chalcogenide glasses are being developed for direct-emission MIR fibre lasers. The true Pr3+ absorption cross-section in the 3.5-6 µm wavelength region of a Pr3+-doped (500 ppmw of Pr3+ i.e. 9.47 x 1019 Pr3+ ions cm-3) GeAsGaSe host-glass is presented, after numerically removing the underlying, extrinsic vibrational absorption due to [H-Se-] contamination of the host-glass.